Interactions of a paracyclophane-based conjugated oligoelectrolyte with biological membranes. Issue 70 (29th November 2018) - Limwongyut, Jakkarin; Liu, Yang; Chilambi, Gayatri Shankar; Seviour, Thomas; Hinks, Jamie; Mu, Yuguang; Bazan, Guillermo C.
Abstract : We report a non-planar conjugated oligoelectrolyte as a membrane permeabilizing material and its membrane interactions compared to the linear analog. Abstract : A three-dimensional conjugated oligoelectrolyte (COE) bearing a [2.2]paracyclophane unit (COE2-3-pCp) was synthesized. Its biological activity was determined both in vivo and in silico within the context of membrane perturbation and biocompatibility. Molecular dynamics simulations indicate that, compared to its linear analog (COE2-3C), COE2-3-pCp introduces more lipid disorder with higher extent of membrane thinning. COE2-3-pCp also exhibits a higher MIC towards E. coli K12 and yeast, while maintaining similar levels of membrane permeabilization. These findings suggest a new design of COEs as biocompatible cell permeabilizers.